2016
DOI: 10.1371/journal.pone.0159950
|View full text |Cite
|
Sign up to set email alerts
|

The Facial Appearance of CEOs: Faces Signal Selection but Not Performance

Abstract: Research overwhelmingly shows that facial appearance predicts leader selection. However, the evidence on the relevance of faces for actual leader ability and consequently performance is inconclusive. By using a state-of-the-art, objective measure for face recognition, we test the predictive value of CEOs’ faces for firm performance in a large sample of faces. We first compare the faces of Fortune500 CEOs with those of US citizens and professors. We find clear confirmation that CEOs do look different when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 40 publications
5
56
0
Order By: Relevance
“…Despite their poor predictive validity, face judgments influence decisions ranging from the relatively trivial choice of which apartment to rent (which might determine the fate of the next vacation; Ert et al, 2016), to the selection of a CEO (which might determine the fate of a company; Gomulya et al, 2016;Graham, Harvey, & Puri, 2017;Stoker, Garretsen, & Spreeuwers, 2016), to the sentencing of a criminal (which might determine the fate of a human being; Blair, Judd, & Fallman, 2004;Eberhardt et al, 2006; J. P. Wilson & Rule, 2015). It may thus not be surprising that researchers have called for a more nuanced understanding of why people persistently rely on face judgments (Olivola et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Despite their poor predictive validity, face judgments influence decisions ranging from the relatively trivial choice of which apartment to rent (which might determine the fate of the next vacation; Ert et al, 2016), to the selection of a CEO (which might determine the fate of a company; Gomulya et al, 2016;Graham, Harvey, & Puri, 2017;Stoker, Garretsen, & Spreeuwers, 2016), to the sentencing of a criminal (which might determine the fate of a human being; Blair, Judd, & Fallman, 2004;Eberhardt et al, 2006; J. P. Wilson & Rule, 2015). It may thus not be surprising that researchers have called for a more nuanced understanding of why people persistently rely on face judgments (Olivola et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Haselhuhn, Ormiston, and Wong (2015) summarize that fWHR is a small but a significant predictor of men's aggression. In contrast, Stoker, Garretsen, and Spreeuwers (2016) run principal component analysis (PCA) based on the intensities of pixels of the face pictures, using a sample of CEOs and non-CEOs. They find that CEO faces are significantly 7 We deeply appreciate the advice of Christian Leuz for this part of our study.…”
Section: Introductionmentioning
confidence: 99%
“…People in certain professions seem to be in some way similar looking. For example, it has been shown that business leaders look different from the general public or university professors, and this seems not to be related to the level of their competence (Stoker, Garretsen, & Spreeuwers, 2016). On the other hand, research has shown that in some cases it is the context which makes significant contributions in judgments.…”
Section: Discussionmentioning
confidence: 99%